Information consumption on Twitter in times of the Russia-Ukraine war - Perez-Cepeda, Maximiliano; Carvache-Francob, Mauricio; Bustamante-Ubillad, Miguel A.; Carvache-Franco, Wilmer; Carvache-Franco, Orly (Taylor and Francis, 2025)
The objective of this study is to delineate the sociocultural influences present during the Russia-Ukraine conflict and that have caused significant economic, commercial and financial shocks. The research has a qualitative approach. Utilizing netnography as the research methodology, Twitter® serves as the primary data capture instrument, where we systematically collect tweets through RStudio and subsequently analyze them through thematic coding in ATLAS.ti to identify sociocultural patterns. We use an accepted model that describes sociocultural factors to analyze the flow of messages posted on Twitter. The composition of messages represents a form of pragmatic competence that exposes underlying sociocultural influences. The categorization and classification of data underlie the analysis of tweets. The discussion revolves around the Russia-Ukraine war, information consumption and sociocultural factors. We constrained the investigation to the Twitter social platform and individuals who engage with the @ wto handle, the verified profile of the World Trade Organization. This study’s primary contributions pertain to establishing the link between sociocultural factors that manifest during a state of war (Russia-Ukraine) and the proposed model that characterizes such influences.

El objetivo de este estudio es delimitar las influencias socioculturales presentes durante el conflicto entre Rusia y Ucrania que han provocado importantes repercusiones económicas, comerciales y financieras. La investigación adopta un enfoque cualitativo. Utilizando la netnografía como metodología de investigación, Twitter® sirve como principal instrumento de captura de datos, donde recopilamos sistemáticamente tweets a través de RStudio y posteriormente los analizamos mediante codificación temática en ATLAS.ti para identificar patrones socioculturales. Utilizamos un modelo aceptado que describe factores socioculturales para analizar el flujo de mensajes publicados en Twitter. La composición de los mensajes representa una forma de competencia pragmática que expone influencias socioculturales subyacentes. La categorización y clasificación de los datos sustentan el análisis de los tweets. La discusión gira en torno a la guerra entre Rusia y Ucrania, el consumo de información y los factores socioculturales. Limitamos la investigación a la plataforma social Twitter y a las personas que interactúan con la cuenta @wto, el perfil verificado de la Organización Mundial del Comercio. Las principales contribuciones de este estudio se refieren a establecer el vínculo entre los factores socioculturales que se manifiestan durante un estado de guerra (Rusia-Ucrania) y el modelo propuesto que caracteriza dichas influencias.
Keywords: Russia-Ukraine war; Netnography; Sociocultural factors; Information consumption; Twitter; Guerra ruso-ucraniana; Netnografía; Factores socioculturales; Consumo de información; https://purl.org/pe-repo/ocde/ford#5.02.04